The Effect of Fuel Mix, Moderated by Indonesia Crude Price and Foreign Exchange, and Power Losses on Profitability of PT PlN (PERSERO) - Rofik, Ahmad; Syah, Tantri Yanuar Rahmat (International Journal of Energy Economics and Policy, 2020)
Like any other corporate, state owned enterprises (SOE) main objective is to achieve optimum profit to ensure its sustainability. In Indonesia, electricity business in run by PT PLN (Persero), a corporate owned 100% by Government of Indonesia. Thus, PLN should maximize its effort on cost reduction and sales volume optimization to ensure its profitability growth. Looking at the structure of operational cost and revenue, this study aims to explore the effect of fuel mix and power losses on profitability (operating profit/loss) of PLN, where the moderating role of Indonesia crude price (ICP) and exchange rate on fuel mix effect toward profitability also take into account. By using moderated regression analysis (MRA), this study found out that the effect of fuel mix on profitability, and power losses on PLN’s profitability exist negatively. ICP and exchange rate also strengthen the effect of fuel mix on PLN’s profitability. This study suggested PLN to continue exploring ways to optimize its fuel mix and power losses, as well as increasing sales volume. This could not be done without Government intervention that favors PLN i.e., tariff adjustment or incentives, especially when exchange rate and ICP value worsen. This is to ensure that PLN has a healthy financial sustainability. Keywords: PT PLN (Persero), Electricity Tariff, Fuel Mix, Indonesia Crude Price, Exchange Rate, Power Losses, Profitability JEL Classifications: E3, L11, M11, R32, G39 DOI: https://doi.org/10.32479/ijeep.9575